EVALUATION OF PATIENTS WITH ORGANOPHOSPHATE POISONING IN THE EMERGENCY DEPARTMENT: A RETROSPECTIVE TWO-CENTER STUDY - Abdussamed Vural; Turgut Dolanbay; Levent Şahin; Mustafa Cihan Altay; Hayri Canbaz (Sabiad)
Objective: The widespread use of organophosphates (OP) as pesticides in global agriculture, pose significant health risks in both developing and industrialized nations. Exposure through ingestion, occupational contact, and suicide attempts leads to high morbidity and mortality. This study will retrospectively analyze the demographic, clinical, and laboratory characteristics of adult patients aged 18 years and older who presented to emergency departments.Material and Methods: The study is a two-center retrospective analysis of the Niğde Ömer Halisdemir University Training and Research Hospital, Clinic of Emergency Medicine and Kafkas University Health Practice and Research Hospital, Clinic of Emergency Medicine. Patient data, including demographics, clinical details, and laboratory parameters, were recorded. Analysis covered routine blood tests, pseudocholinesterase levels, and electrocardiography findings. Patients diagnosed with OP poisoning (international classification of diseases (ICD) code T60.0) between 15 June 2020 and 15 June 2023 were included in the study.Results: The study included 24 patients meeting inclusion and exclusion criteria. Oral exposure (41.7%) and inhalation (25%) were common routes. The hospitalization rate was 91.7%, with only 4.2% requiring intubation. No in-hospital mortality occurred. Pseudocholinesterase levels correlated negatively with pH, bicarbonate, anion gap and positively with c-reactive protein (CRP). Duration of hospital stays was negatively correlated with Glasgow coma scale (GCS), pH, bicarbonate, and positively correlated with the anion gap.Conclusion: This retrospective, two-center study provides comprehensive insights into the demographic profiles, clinical manifestations, and treatment outcomes of adult patients presenting with OP poisoning in emergency departments. In our study, most organophosphate poisonings were accidental. In this respect, it is important to provide safety equipment, safe farming conditions, limited access to hazardous substances, emergency education, public health campaigns and safe work practices in factories and farms to prevent organophosphate poisoning. Furthermore, this study underlines the importance of assessment of clinical parameters such as GCS, pH and HCO3 in predicting the severity and duration of hospitalization.